Towards a Resilient and Sustainable Agri-Food System by 2025 in Nigeria and Sub-Saharan Africa - Agricultural Policy Research Network (APRNet, 2022)
The 7th APRNet Agricultural Policy Stakeholders’ Forum and 1st Annual International Conference were held at the Hotel Benizia, Asaba, Delta State, Nigeria from Wednesday, 1st to Friday, 3rd June 2022. The theme of the Forum was: “Towards a Resilient and Sustainable Agri-Food System by 2025 in Nigeria and Sub-Saharan Africa”. The Forum was organized in collaboration with the Job & Wealth Creation Office, Delta State Nigeria, the International Food Policy Research Institute (IFPRI) under the USAID/Nigeria Feed the Future Agriculture Policy Activity, and PILAF-NIGERIA. A total of 178 participants were in attendance and 51 papers were presented at the parallel sessions on 3rd June 2022.